A randomized double-blinded controlled trial comparing ultrasound-guided versus conventional injection for caudal block in children undergoing infra-umbilical surgeries - Navya Kollipara; V Rajesh Kumar Kodali; Aruna Parameswari (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Caudal epidural block is widely used in pediatric surgeries to provide intraoperative and postoperative analgesia in infra-umbilical surgeries. The conventional technique involves the risk of multiple punctures and other complications such as dural puncture, vascular puncture, and intraosseous injection. Material and Methods: Around 106 children aged between 6 months to 10 years belonging to ASA class I-II scheduled for elective infra-umbilical surgeries were included after obtaining written informed consent from parents/guardians. All children were randomized into two groups: ultrasound-guided (Group U) or conventional caudal group (Group C). All were premedicated with oral midazolam and inhalational induction was done with oxygen and 6-8% sevoflurane. Caudal block of 1 mL/kg of 0.125% bupivacaine was administered in both groups. The primary outcome assessed was 1st puncture success rate and the secondary outcomes assessed were number of skin punctures, block performing time, and block success rate. Results: Group U had a higher first puncture success rate (P = 0.001) than Group C (90.6% v/s 64.2%) and was statistically significant. The number of punctures were significantly less (P = 0.01) in Group U (1.09 ± 0.295) than Group C (1.45 ± 0.667). Block performing time was significantly higher (P = 0.0005) in Group U (53.19 ± 10.97 s) than Group C (30.34 ± 7.34 s). There was no difference in the overall block success rate between the groups (98.1% v/s 100%). Conclusion: Ultrasound-guided caudal injection increases the first puncture success rate and decreases the number of punctures required compared to conventional caudal block in pediatric infra-umbilical surgeries.